1997
DOI: 10.1128/jvi.71.7.5277-5286.1997
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin-esterase, a novel structural protein of torovirus

Abstract: We have characterized the 3-most 3 kb of the genome of bovine torovirus (BoTV) strain Breda. A novel 1.2-kb gene, located between the genes for the membrane and nucleocapsid proteins, was identified. This gene, the 3-most 0.5 kb of which is also present in the genome of the equine torovirus isolate Berne virus (BEV), codes for a class I membrane protein displaying 30% sequence identity with the hemagglutinin-esterases (HEs) of coronaviruses and influenza C viruses. Heterologous expression of the BoTV HE gene y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
89
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 61 publications
3
89
0
1
Order By: Relevance
“…The length of the HE gene was 9 nts longer from that reported previously for BoTV-1 and BoTV-2 (Cornelissen et al, 1997;Duckmanton et al, 1998a,b), extending the protein sequence by 3 amino acids. A stretch of seven thymidine residues (27,721), as opposed to eight in the previously reported sequence, is responsible for this difference.…”
Section: Comparison Of the 3 End Of Botv-1 Sequence With That Previoumentioning
confidence: 55%
See 1 more Smart Citation
“…The length of the HE gene was 9 nts longer from that reported previously for BoTV-1 and BoTV-2 (Cornelissen et al, 1997;Duckmanton et al, 1998a,b), extending the protein sequence by 3 amino acids. A stretch of seven thymidine residues (27,721), as opposed to eight in the previously reported sequence, is responsible for this difference.…”
Section: Comparison Of the 3 End Of Botv-1 Sequence With That Previoumentioning
confidence: 55%
“…The complete genome sequence of EqTV has yet to be published, although Smits et al (2003) reported the completion of the EqTV genome sequence in a recent study of torovirus field variants. The published sequence of BoTV is limited to that of the structural genes, which account for approximately 7.5 kb of the 3 end of the genome (Cornelissen et al, 1997;Duckmanton et al, 1998a,b). Consequently, the genus Torovirus remains the only genus within the order Nidovirales without a representative complete genome sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The variability of the HE gene within toroviruses is also remarkable. The HE gene is present in porcine, bovine, equine, and putative human toroviruses (Cornelissen et al, 1997;Duckmanton et al, 1999;Kroneman et al, 1998). Most newly characterized bovine torovirus variants seem to have emerged from a genetic exchange, during which the 3 end of the HE gene, the N gene, and the 3 nontranslated region of a bovine virus (Breda type strain) have been swapped for those of a porcine torovirus.…”
Section: Virus-specific Accessory Genes: Fast Adaptability To a New Nmentioning
confidence: 99%
“…Toroviruses within the family Coronaviridae are spherical, oval, elongated, or kidney-shaped enveloped viruses that possess a positive-sense single-stranded, polyadenylated RNA genome of approximately 25-30 kb in length (Cornelissen et al, 1997;Horzinek, 1999;Snijder and Horzinek, 1993). Toroviruses have been detected in normal horses as well as in humans, cattle, pigs, and recently in turkeys with diarrhea (Ali and Reynolds, 2000;Beards et al, 1986;Duckmanton et al, 1997Duckmanton et al, , 1998aKroneman et al, 1998;Woode, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no reports of BToV infections in South Korea. Since the molecular analysis of the BToV has only been carried out in North American, European and Japanese BToV strains (Cornelissen et al, 1997;Draker et al, 2006;Duckmanton et al, 1998b;Gonzálex et al, 2003;Haschek et al, 2006;Hoet et al, 2002Hoet et al, , 2003aIto et al, 2007;Smits et al, 2003), it is unclear if the BToVs circulating in other countries have distinct genetic characteristics. This paper reports the detection of BToV shedding in diarrheic calves using RT-PCR and nested PCR, along with the genetic diversity of the BToV strains based on a partial BToV membrane (M) gene.…”
Section: Introductionmentioning
confidence: 99%